INFANTILE ALEXANDER’S DISEASE: A CASE WITH CHARACTERISTIC MRI FEATURES - Mazhar, Naveed; Saeed, Uzma (Journal of Ayub Medical College Abbottabad, 2016)
Alexander disease, less commonly known as fibrinoid leukodystrophy is an extremely rare, non-familial, progressive, lethal leukodystrophy which is characterized predominantly by abnormalities of white matter in bilateral frontal regions. It usually presents early within first 2 years of life with clinical features of macrocephaly, recurrent seizures and psychomotor retardation. Diagnosis of this white matter disorder is possible with certain features seen on magnetic resonance imaging (MRI), even without the need for histological confirmation. Our case is a one year old male infant who presented with repeated episodes of focal seizures to the paediatrician. He was referred for an MRI and subsequently based on typical MRI findings the diagnosis of Alexander disease was made.